THE INFLUENCE OF DIVIDEND POLICY, INVESTMENT OPPORTUNITIES AND PROFITABILITY ON COMPANY VALUE(Study of Manufacturing Companies Listed on the IDX 2018-2022) - A.A. Sagung Istri Pramanaswari (CV. Adiba Aisha Amira, 2025)
This research aims to determine the influence of dividend policy, investment opportunities and profitability on company value in manufacturing companies listed on the Indonesian stock exchange for the period 2018 to 2022. This research uses quantitative methods with a descriptive approach. Through partial t-test and simultaneous f test, it is known that partially dividend policy has a significant influence on company value with a significance value of 0.000. Investment opportunities have a significant influence on company value with a significance value of 0.007 and profitability has a significant influence on company value with a significance value of 0.000. Furthermore, together dividend policy, investment opportunities and profitability have a significant simultaneous influence on the company value of manufacturing companies listed on the Indonesian stock exchange for the period 2018 to 2022.